2018
DOI: 10.1073/pnas.1719897115
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of dopamine D 2 receptors from parvalbumin interneurons in mouse causes schizophrenia-like phenotypes

Abstract: Excessive dopamine neurotransmission underlies psychotic episodes as observed in patients with some types of bipolar disorder and schizophrenia. The dopaminergic hypothesis was postulated after the finding that antipsychotics were effective to halt increased dopamine tone. However, there is little evidence for dysfunction within the dopaminergic system itself. Alternatively, it has been proposed that excessive afferent activity onto ventral tegmental area dopaminergic neurons, particularly from the ventral hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…2). Genetically induced PV-neuron-specific hypo-function leads to an elevated excitation and inhibition ratio in the ventral hippocampus 74 . Recent studies have suggested that chronic stresses also induce hypo-function of interneurons, including PV neurons, and hyperactivity of excitatory neurons in the hippocampus, cortex, and amygdala 75 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Genetically induced PV-neuron-specific hypo-function leads to an elevated excitation and inhibition ratio in the ventral hippocampus 74 . Recent studies have suggested that chronic stresses also induce hypo-function of interneurons, including PV neurons, and hyperactivity of excitatory neurons in the hippocampus, cortex, and amygdala 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that chronic stresses also induce hypo-function of interneurons, including PV neurons, and hyperactivity of excitatory neurons in the hippocampus, cortex, and amygdala 75 . Exacerbated pyramidal neuron activity in the ventral hippocampus may underlie the aberrant modulation of DA release from dopaminergic neurons of the midbrain after exposure to an adverse environmental stimulus, such as amphetamine 74,76,77 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine (DA), a typical neurotransmitter, plays a critical role in the central nervous systems to control reward-related behaviors, movement initiation, release of hormones, etc. [1][2][3] An abnormal level of DA can lead to severe diseases, such as Parkinson's, [4] schizophrenia, [5] and depression. [6] The reliable and accurate detection of DA, however, is not easy.…”
Section: Highly Sensitive and Selective Electrochemical Detection Of mentioning
confidence: 99%
“…Although, these studies elegantly outline the role of sub-regions in the PFC or striatum, few studies have explored the neuronal and molecular diversity of PFC pyramidal neurons involved in regulating motivation and cognition. Dopamine and its receptors in the PFC also regulate motivated behavior and cognitive flexibility (Barker et al, 2013;Goldman-Rakic, 1998;Hitchcott et al, 2007;Natsheh and Shiflett, 2018;Ott and Nieder, 2019) Dopamine activates D1 (stimulatory Gαs-coupled) and D2 (inhibitory Gαi-coupled) class of receptors in the PFC, which modulate the activity of both pyramidal neurons and interneurons (Ferguson and Gao, 2018;Santana et al, 2009;Tomasella et al, 2018;O'Donnell, 2004, 2007). Moreover, pharmacological targeting of D1Rs or D2Rs, or genetic deletion of D2Rs in the PFC can regulate dopamine-dependent behaviors such as locomotion and goal-directed behavior (Barker et al, 2013;Del Arco et al, 2007;Hitchcott et al, 2007;Natsheh and Shiflett, 2018;Tomasella et al, 2018;Urs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%